Pengembangan E-Modul dengan Pendekatan STEM untuk Memfasilitasi Kemampuan Berpikir Kritis Siswa pada Materi Trignometri - Khizanaturrohmah Nur Maziyah; Fina Hanifa Hidayati (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
Critical thinking is one of the abilities that can be stimulated through learning mathematics by using an appropriate approach. One approach that can facilitate critical thinking skills is the STEM approach. To implement this approach, teaching materials are needed as support. This study aims to find out how to develop a valid e-modules as teaching materials with a STEM approach to facilitate students' critical thinking skills on trigonometry. The method used is Research and Development (R&D) with the PPE development model (Planning, Production, Evaluation). At the planning stage, curriculum analysis and analysis of class X MIA MAN 2 Indramayu were carried out. In the production stage, the creation and collection of data needed by the e-module is carried out, compiling the e-module, preparing links to connect to the required web page, and packaging the pdf format module into an electronic module (e-module). In the evaluation stage, an assessment of the quality of the e-module was carried out by material and media experts from the mathematics lecturer at UIN Sunan Kalijaga Yogyakarta and the mathematics teacher at MAN 2 Indramayu. The quality assessment of this e-module shows an ideal percentage value which is included in the